2001
DOI: 10.1128/jvi.75.19.9297-9301.2001
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen-Binding Activity of Neuraminidase Determines the Pathogenicity of Influenza A Virus

Abstract: When expressed in vitro, the neuraminidase (NA) of A/WSN/33 (WSN) virus binds and sequesters plasminogen on the cell surface, leading to enhanced cleavage of the viral hemagglutinin. To obtain direct evidence that the plasminogen-binding activity of the NA enhances the pathogenicity of WSN virus, we generated mutant viruses whose NAs lacked plasminogen-binding activity because of a mutation at the C terminus, from Lys to Arg or Leu. In the presence of trypsin, these mutant viruses replicated similarly to wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 34 publications
5
87
0
Order By: Relevance
“…Interestingly, however, PAR1-AP did promote PLG-dependent HA cleavage in lung epithelial cultures, suggestive of a possible interaction of PAR1 signaling with the ability of IAV to become infectious and hence replicate. These findings are consistent with the prior observation that PLG contributes to the pathogenesis of IAV infection (27,28). Additionally, PAR1 signaling may promote PLG activation to plasmin (29,30), thereby providing a possible link to increased HA cleavage and IAV production.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, however, PAR1-AP did promote PLG-dependent HA cleavage in lung epithelial cultures, suggestive of a possible interaction of PAR1 signaling with the ability of IAV to become infectious and hence replicate. These findings are consistent with the prior observation that PLG contributes to the pathogenesis of IAV infection (27,28). Additionally, PAR1 signaling may promote PLG activation to plasmin (29,30), thereby providing a possible link to increased HA cleavage and IAV production.…”
Section: Discussionsupporting
confidence: 81%
“…PLG is an important mediator of lung inflammation (25,26) and is known to influence IAV virulence (27,28). Importantly, PLG binding to cells and activation may be controlled by PAR1 signaling (29,30).…”
Section: Par1 Contributes To the Pathogenesis Of Iav Infectionmentioning
confidence: 99%
“…It is believed that tissue penetration and dissemination are facilitated by the acquisition of Pg on the bacterial surface and subsequent activation of this surface-associated Pg by a host-derived Pg activator such as tissue Pg activator (tPA) or urokinase Pg activator. Pg binding is used by the influenza A virus to enter host cells (17). The prion protein PrP(Sc) that is associated with transmissible spongiform encephalopathy has also been reported to bind Pg (18), although the physiological significance has been questioned (19).…”
mentioning
confidence: 99%
“…Recent work from our laboratories using such a surrogate system demonstrated that the NS1 protein of influenza A/Brevig Mission/1/18 virus expressed in the context of a recombinant influenza A/WSN/33 virus (WSN) was a more potent alpha/beta interferon (IFN-␣/␀) antagonist than the parental WSN NS1 protein in infected human respiratory epithelial (A549) cells (29). In addition to the IFN-antagonistic properties of the NS1 protein, the surface glycoproteins of influenza virus (HA and NA) have been shown to be important virulence factors in mice and birds (30,31,33,41,52,61,65,71,73). As the HA and NA sequences of the 1918 virus have been elucidated (57, 58), we next determined the contribution of the 1918 HA and NA genes to viral pathology in the mouse model by examining infection outcome, lung histology, and gene expression changes by expression microarray analysis.…”
mentioning
confidence: 99%